A power flow solvability identification and calculation algorithm using evolutionary programming (EP) / Kahardi Muhammad Talib - Muhammad Talib, Kahardi (2016)
Power flow is the solution for the static operating condition of an electric-power transmission system with a set of system parameters and properties. This paper proposes the Evolutionary Programming (EP) technique to estimate the power flow solvability by using IEEE 6-bus Reliability Test System (RTS).